2011
DOI: 10.4161/cc.10.14.16494
|View full text |Cite
|
Sign up to set email alerts
|

From Plk1 to Plk5

Abstract: Mammalian polo-like kinases (Plks) are characterized by the presence of an N-terminal protein kinase domain and a C-terminal polo-box domain (PBD) involved in substrate binding and regulation of kinase activity. Plk1-4 have traditionally been linked to cell cycle progression, genotoxic stress and, more recently, neuron biology. Recently, a fifth mammalian Plk family member, Plk5, has been characterized in murine and human cells. Plk5 is expressed mainly in differentiated tissues such as the cerebellum. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
145
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(147 citation statements)
references
References 82 publications
1
145
1
Order By: Relevance
“…In mammals, there are five paralogs of polo-like kinases, PLK1-5, although key kinase residues are absent in PLK5 (de Cárcer et al, 2011). PLK1 is the mammalian ortholog of Cdc5p and is termed a 'master regulator' of cell division (de Cárcer et al, 2011). To probe the role of PLK in desynapsis, we have taken advantage of the nearly synchronous first wave of spermatogenesis in mice (Bellvé et al, 1977;Cohen et al, 2006) and the ability to isolate highly enriched pachytene spermatocytes and induce meiotic prophase exit ex vivo with the phosphatase inhibitor okadaic acid (OA) .…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, there are five paralogs of polo-like kinases, PLK1-5, although key kinase residues are absent in PLK5 (de Cárcer et al, 2011). PLK1 is the mammalian ortholog of Cdc5p and is termed a 'master regulator' of cell division (de Cárcer et al, 2011). To probe the role of PLK in desynapsis, we have taken advantage of the nearly synchronous first wave of spermatogenesis in mice (Bellvé et al, 1977;Cohen et al, 2006) and the ability to isolate highly enriched pachytene spermatocytes and induce meiotic prophase exit ex vivo with the phosphatase inhibitor okadaic acid (OA) .…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian polo-like kinase 1 (PLK1) belongs to a family of 5 serine/threonine kinases (de Carcer et al, 2011). It consists of a kinase domain (KD) at the N-terminus and a highly conserved polo-box domain (PBD) composed of 2 polo boxes near the C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the PBD plays a crucial role in substrate binding and regulation of kinase activity (Lowery et al, 2005). As a master regulator of cell division, PLK1 functions in almost every stage of cell division including mitotic entry, centrosome maturation, bipolar spindle formation, chromatid segregation, mitotic exit, and cytokinesis (de Carcer et al, 2011). Moreover, its role is not limited to mitosis and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this compound was not reported according to SciFinder. Its purity was reconfirmed by 1 H NMR ( Figure S2). [a] BI 2536 was used as a positive control (IC 50 : 11.5 AE 1.3 nm); data are the mean AE SD of three independent experiments.…”
Section: In Vitro Inhibition Of Full-length Plk1 Activitymentioning
confidence: 99%
“…[1,2] It is well characterized and is overexpressed in many cancers. [3] The depletion of Plk1 induces apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%